How general is the natural frequency effect? The case of joint probabilities - Stegmüller, Nathalie; Binder, Karin; Krauss, Stefan (Frontiers in Psychology, 2024)
Natural frequencies are known to improve performance in Bayesian reasoning. However, their impact in situations with two binary events has not yet been completely examined, as most researchers in the last 30 years focused only on conditional probabilities. Nevertheless, situations with two binary events consist of 16 elementary probabilities and so we widen the scope and focus on joint probabilities. In this article, we theoretically elaborate on the importance of joint probabilities, for example, in situations like the Linda problem. Furthermore, we implemented a study in a 252 design with the factors information format (probabilities vs. natural frequencies), visualization type ("Bayesian text" vs. tree diagram vs. double tree diagram vs. net diagram vs. 22 table), and context (mammography vs. economics problem). Additionally, all four joint questions (P(𝐴𝐵), P(𝐴 ̅ 𝐵), P(𝐵 ̅ 𝐴 ̅ ), P(𝐵 ̅ 𝐴)) were asked for. The main factor of interest was whether there is a format effect in the five visualization types named above. Surprisingly, the advantage of natural frequencies was not found for joint probabilities and, most strikingly, the format interacted with visualization type. Specifically, while people's understanding of joint probabilities in a double tree seems to be worse than the understanding of the corresponding natural frequencies (and, thus, the frequency effect holds true), the opposite seems to be true in the 2×2 table. Thus, the advantage of natural frequencies compared to probabilities in typical Bayesian tasks cannot be found in the same way when joint probability or frequency tasks are asked.